A systematic literature review to understand the difference between critical factors affecting the national election and state elections in India - Chatterjee, Joydeep; Dutta, Gautam (Frontiers in Political Science, 2024)
Introduction This study aims to understand the dominant factors of political marketing strategies to influence voters in the national and state elections in India. To identify them, we have reviewed literature of different nations (both developed and developing) across the world and India. Methods We have defined specific criteria and search terms to first identify the relevant studies that have focused on the influencing factors in the global and Indian political marketing landscape. After identifying these factors, we gleaned the key takeaways in terms of the influencing factors from all those studies and discussed the different emerging trends of shifting power from party brand to leadership brand in the national elections. We have also analyzed the impact of different factors such as party leader or candidate's personality, party policy and ideology, use of social media as a campaigning tool, and campaign messaging and platform on the national and state elections over the years Results and discussions We found that for the national elections, partly leadership and use of social media are critical factors, while for the state elections, party policy and ideology with on-ground campaigns have a significant influence on voters.